ALGORITMA PENGENALAN POLA BINTANG UNTUK DETEKSI POSISI BINTANG PADA STAR SENSOR SATELIT LAPAN - Saifudin, M. Arif; Triharjanto, Robertus Heru (BRIN Publishing, 2010)
Star sensor is a high accuracy sensor for a satellite attitude determination. This sensor identifies the position of stars in celestial map by comparing the position of stars on its active sensor with the star position data contained in its catalogue. An algorithm is needed to recognize the star pattern imaged by sensoring and calculating the position of the stars. An efficient and accurate algorithm is needed to improve the performance of the star sensor for satellite attitude determination. A simple star pattern recognition algorithm uses the neighbourhood technique. The first approach of algorithm is detecting the brightest star and its neigbours in the sensor Field of View (FOV) and identifying whether the stars in image sensor are fit to the star pattern in the catalogue.The simple catalogue used contains the star position and all its neighbouring stars within particular distance in the scope of FOV. Test result showed that neighbours technique has an accuracy below 1 arc min which correspond to the typical accuracy value of star sensor.